Celastrol Alleviates Airway Hyperresponsiveness and Inhibits Th17 Responses in Obese Asthmatic Mice - Zeyu Zeng; Xixi Lin; Rongying Zheng; Hui Zhang; Weixi Zhang (Frontiers Media S.A., 2018)
Severe airway hyperresponsiveness (AHR) is a clinical feature of asthma, which has been associated with obesity and has shown a poor response to standard asthma treatments such as glucocorticoids. Numerous studies have shown that Interleukin (IL)-17 producing CD4+T cells (Th17 cells), which could be inhibited by celastrol, is essential in mediating steroid-resistant AHR. The following study investigates the impact of celastrol and its mechanism on the regulation of AHR in murine model of obesity and asthma. C57BL/6 mice were sensitized by intraperitoneal injection of ovalbumin (OVA) on day 1 and 13 starting from 12th week, which was followed by aerosol OVA challenge that lasted for 30 min per daily for 7 consecutive days starting from 16th week. Diet-induced obesity (DIO) mice were fed a high fat diet (HFD) for 16 weeks. Celastrol was administrated orally for 7 consecutive days, 30 min before every challenge in DIO-OVA-induced mice. Lung functions were analyzed by measuring the airway resistance (Rn) and methacholine (MCh) AHR, while H&E staining was used to examine histological changes in the lungs. Immunohistochemistry was used to observe IL-17A protein in lung tissues; flow cytometry to detect the proportion of Th17 cells in CD4+T cells. The concentration of cytokines IL-17A in serum was assessed by standardized sandwich ELISA, while the expression of IL-17A mRNA in lung was examined by quantitative real-time RT-PCR. Briefly, our data indicated that celastrol reduced body mass in DIO-OVA-induced obesity and asthma. Both baseline Rn and MCh AHR were significantly lower in celastrol group. Moreover, celastrol treatment decreased the frequency of Th17 cell expansion and reduced the production of IL-17A in both lung and serum. To sum up, our findings indicated that Th17 and its cytokine measured in the spleen and lung were closely associated with AHR. In addition, celastrol has shown the ability to suppress AHR through Th17 inhibition in obese asthmatic mice.